The PRESENTATION AND OUTCOMES OF AORTOFEMORAL BYPASS SURGERY IN PATIENTS WITH AORTOILIAC OCCLUSIVE DISEASE. FOUR YEARS’ EXPERIENCE AT A TERTIARY CARE HOSPITAL - Siddique, Muhammad Khalid; Ahmed, Waqas; Butt, Khalid Pervaiz; Akhtar, Khalid Ibrahim; Khalid, Hamna; Khan, Muhammad Tariq (Pakistan Armed Forces Medical Journal, 2020)
Objective: To highlight the presentation and outcomes of Aortofemoral bypass surgery at a tertiary care hospital.Study Design: Prospective observational study.Place and Duration of Study: Vascular Surgery department, Combined Military Hospital Lahore, from Jan 2015to Dec 2019.Methodology: A total of 23 patients between 50-80 years of age presenting with critical limb ischemia due toAortoiliac occlusive arterial disease type C or D of Trans-Atlantic inter Society Consensus (TASC) II classificationconfirmed on CT Angiogram, were included in the study. The clinical presentation, co-morbid illnesses, historyof smoking, obesity, post operative patency of graft, wound infection, amputation rates, and mortality weredocumented on a structured proforma. All patients were followed up at 1, 6, 12 and 24 months of surgery.Outcomes were assessed in terms of graft patency, wound infection, limb survival, amputations and mortality.Data was analyzed by SPSS version 23.0.Results: The mean age of patients was 71.04 ± 7.29 years. Most patients presented with rest pain (56.5%). Thefrequency of smokers was 78.3% while 34.8% patients had both diabetes mellitus and ischemic heart disease.Hyperlipidemia was present in 30.4% patients. Two patients (8.7%) developed superficial surgical site infection.The limb salvage rate was 95.7% and the mortality rate was 4.3%.Conclusion: Aortofemoral bypass surgery is a safe and highly effective treatment modality for the management of aortoiliac occlusive arterial disease in experienced hands. Limb salvage can be successfully achieved in more than 95% cases.Keywords: ,, ,, .